Age and Growth of Red Porgy, Pagrus pagrus from the Island of Gökçeada, North Aegean Sea - Hakan Ayyıldız; Aytaç Altın; Bayram Kızılkaya (Aquatic Sciences and Engineering)
The aim of this study was to describe the age, growth and relationships between otolith morphometry and fish length, weight and age of the red porgy, Pagrus pagrus. This study was carried out from the shores of Gizli liman to Kefalos Cape in the north of Gökçeada Island, between March and June 2018. The samples were collected at depths of 40-120 m by long lines. The 66 individuals obtained from red porgy ranged in total length (TL) from 13.5 to 50 cm. The calculated length– weight relationship was determined as W=0.016TL2.9653 (R2=0.98). Individual ages were macroscopically determined by counting the annuli of sagittal otoliths. Estimated ages ranged from 1–12 years. The von Bertalanffy growth curve was fitted to the age/total length data as follows: L∞=51.48 cm, K= 0.18 and t0=-0.27. The red porgy sagittal otolith length, width and mass were measured between 4.96–14.72 mm, 3.49–7.85 mm and 0.0199–0.2460 g, respectively. No significant differences in otolith morphometry were found between left and right otoliths. This study provides valuable data for the stock assessment of common pandora in the fishing grounds of Gökçeada Island located in the North Aegean Sea.